STATUS GLASA /Ʒ/ U MAKEDONSKOM, SRPSKOM I CRNOGORSKOM JEZIKU (Philological Studies, 2019)
The introductory part of this paper explores the articulatory and acoustic features of the sound //, and raises the issue of its origin and position in Slavic languages. The first part of the main section deals with the distribution of the sound // in several Macedonian dialects, as well as Old and Middle Shtokavian dialects, in Serbia and Montenegro, while the second part establishes the status of the sound// in present-day Standard Macedonian and Serbian. Finally, its sociolinguistic role in the process of the codification of the Montenegrin language is briefly outlined.
Keywords: phonology, sociolinguistics, sound //, Macedonian, Serbian, standardization of the Montenegrin language